Formal recycling of e-waste leads to increased exposure to toxic metals: An occupational exposure study from Sweden - Julander, Anneli; Lundgren, Lennart; Skare, Lizbet; Grandér, Margaretha; Palm, Brita; Vahter, Marie; Lidén, Carola (Environment international, 2014)
Electrical and electronic waste (e-waste) contains multiple toxic metals. However, there is currently a lack of exposure data for metals on workers in formal recycling plants. The objective of this study was to evaluate workers' exposure to metals, using biomarkers of exposure in combination with monitoring of personal air exposure. We assessed exposure to 20 potentially toxic metals among 55 recycling workers and 10 office workers at three formal e-waste recycling plants in Sweden. Workers at two of the plants were followed-up after 6months. We collected the inhalable fraction and OFC (37-mm) fraction of particles, using personal samplers, as well as spot samples of blood and urine. We measured metal concentrations in whole blood, plasma, urine, and air filters using inductively coupled plasma-mass spectrometry following acid digestion. The air sampling indicated greater airborne exposure, 10 to 30 times higher, to most metals among the recycling workers handling e-waste than among the office workers. The exposure biomarkers showed significantly higher concentrations of chromium, cobalt, indium, lead, and mercury in blood, urine, and/or plasma of the recycling workers, compared with the office workers. Concentrations of antimony, indium, lead, mercury, and vanadium showed close to linear associations between the inhalable particle fraction and blood, plasma, or urine. In conclusion, our study of formal e-waste recycling shows that workers performing recycling tasks are exposed to multiple toxic metals. •Workers performing formal recycling tasks are exposed to multiple toxic metals.•V, Sb, In, Pb and Hg showed significant correlations between air and blood/urine.•Significantly higher levels of Cr, Co, Pb, In and Hg was found in recycling workers.•Rare metals such as indium and antimony must be monitored in these settings.